Programmed death ligand‐1 regulates angiogenesis and metastasis by participating in the c‐JUN/VEGFR2 signaling axis in ovarian cancer. Issue 6 (3rd May 2021) - Yang, Yufei; Xia, Lingfang; Wu, Yong; Zhou, Hongyu; Chen, Xin; Li, Haoran; Xu, Midie; Qi, Zihao; Wang, Ziliang; Sun, Huizhen; Cheng, Xi
Abstract: Background: Although programmed cell death‐ligand 1 (PD‐L1) plays a well‐known function in immune checkpoint response by interacting with programmed cell death‐1 (PD‐1), the cell‐intrinsic role of PD‐L1 in tumors is still unclear. Here, we explored the molecular regulatory mechanism of PD‐L1 in the progression and metastasis of ovarian cancer. Methods: Immunohistochemistry of benign tissues and ovarian cancer samples was performed, followed by migration, invasion, and angiogenesis assays in PD‐L1‐knockdown ovarian cancer cells. Immunoprecipitation, mass spectrometry, and chromatin immunoprecipitation were conducted along with zebrafish and mouse experiments to explore the specific functions and mechanisms of PD‐L1 in ovarian cancer. Results: Our results showed that PD‐L1 induced angiogenesis, which further promoted cell migration and invasion in vitro and in vivo of ovarian cancer. Mechanistically, PD‐L1 was identified to directly interact with vascular endothelial growth factor receptor‐2 (VEGFR2) and then activated the FAK/AKT pathway, which further induced angiogenesis and tumor progression, leading to poor prognosis of ovarian cancer patients. Meanwhile, PD‐L1 was found to be regulated by the oncogenic transcription factor c‐JUN at the transcriptional level, which enhanced the expression of PD‐L1 in ovarian cancer. Furthermore, we demonstrated that PD‐L1 inhibitor durvalumab, combined with the antiangiogenic drug, apatinib, could enhance the effect of anti‐angiogenesis and the inhibition of cell migration and invasion. Conclusion: Our results demonstrated that PD‐L1 promoted the angiogenesis and metastasis of ovarian cancer by participating in the c‐JUN/VEGFR2 signaling axis, suggesting that the combination of PD‐L1 inhibitor and antiangiogenic drugs may be considered as a potential therapeutic approach for ovarian cancer patients. Abstract : This manuscript demonstrated that PD‐L1 promoted the angiogenesis and metastasis of ovarian cancer by participating in the c‐JUN/VEGFR2 signaling axis, and suggested that the combination of PD‐L1 inhibitor and antiangiogenic drugs may be considered as a potential therapeutic approach for ovarian cancer patients.